Enhanced Figure of Merit via Hybridized Guided-Mode Resonances in 2D-Metallic Photonic Crystal Slabs - Sarkar, Swagato; Ghosh, Anik Kumar; Adnan, Mohammad; Aftenieva, Olha; Gupta, Vaibhav; Fery, Andreas; Joseph, Joby; Koenig, Tobias A. F. (Advanced Optical Materials, 2022)
Metallic nanostructures are highly attractive for refractive index sensing, as the evanescent field from the associated plasmonic resonances resides in close proximity to the adjacent analyte media. However, this benefit is often reduced due to broad plasmonic lineshapes producing poor quality factors. The rational design provides strategies for narrowing the plasmonic modes by incorporating photonic diffraction, which promotes surface lattice resonances . Due to the stringent parametric dependencies, these resonances in metallic lattices are not always feasible, particularly when a straightforward fabrication route with fewer process steps is desired. Herein, hybridized guided-mode resonance in a 2D-metallic photonic crystal slab (2D-mPhCs) is introduced that ensures high-quality hybrid modes while maintaining a simple fabrication methodology. In direct comparison to its constituent plasmonic and photonic modes, this concept is discussed for sensing applications. The "figure of merit (FOM)" is frequently regarded as a valid metric for measuring sensing performanceensuring high-quality modes with an improved detection limit. The experimental results confirm enhanced FOM (three to six times) for the hybrid modes, in contrast to the constituent counterparts. For optoelectronic applications, such as photodetection and photocatalysis, these hybrid structures with high-quality modes offer a promising platform to harvest light at the metal-semiconductor interfaces.
CRIS-Team WoS Importer:2022-08-19

Exploring Plasmonic Resonances Toward "Large-Scale" Flexible Optical Sensors with Deformation Stability - Ghosh, Anik Kumar; Sarkar, Swagato; Nebel, Lisa Julia; Aftenieva, Olha; Gupta, Vaibhav; Sander, Oliver; Das, Amit; Joseph, Joby; Wiessner, Sven; Koenig, Tobias A. F.; Fery, Andreas (Advanced Functional Materials, 2021)
The next generation of sensors requires a simple yet compact lab on chip-based precise optical detection mechanism where data interpretation can be achieved with minimum effort. Hereby, cost-efficient strategies of manufacturing both propagating surface plasmon polariton (SPP) and localized surface plasmon resonance (LSPR) sensors on flexible platforms are explored via mechanical instabilities and oblique-angled metal evaporation. Centimeter scaled dielectric grating structures produced by plasma oxidation of pre-stressed polydimethylsiloxane film have comprised the substrates, thus imparting inherent flexibility. Subsequently, both continuous and discontinuous 1D-metallic lattices are obtained via vapor deposition of gold at different angles. The optical isotropy (gold surface-grating) and anisotropy (gold edge-grating) are distinctly observed as a difference between forward and backward diffraction efficiencies, backed by analytical correlation to the observed orders. Supported with electromagnetic modeling, the SPP and LSPR excitations are experimentally characterized under reflectance and transmittance measurements, along with a demonstration of their sensing capabilities. The LSPR supported flexible sensor provides superiority in terms of sensitivity, which is investigated under mechanical deformations to exhibit consistency of the resonant wavelength. Such consistency is strategically unraveled via "finite element method" based approaches, thus providing a new paradigm of cost-efficient, large-scaled flexible sensors.
CRIS-Team WoS Importer:2021-05-28

Mechano-tunable chiral metasurfaces via colloidal assembly - Probst, Patrick T.; Mayer, Martin; Gupta, Vaibhav; Steiner, Anja Maria; Zhou, Ziwei; Auernhammer, Gunter K.; Koenig, Tobias A. F.; Fery, Andreas (Nature Materials, 2021)
Dynamic control of circular polarization in chiral metasurfaces is being used in many photonic applications. However, simple fabrication routes to create chiral materials with considerable and fully tunable chiroptical responses at visible and near-infrared wavelengths are scarce. Here, we describe a scalable bottom-up approach to construct cross-stacked nanoparticle chain arrays that have a circular dichroism of up to 11 degrees. Due to their layered design, the strong superchiral fields of the inter-layer region are accessible to chiral analytes, resulting in a tenfold enhanced sensitivity in a chiral sensing proof-of-concept experiment. In situ restacking and local mechanical compression enables full control over the entire set of circular dichroism characteristics, namely sign, magnitude and spectral position. Strain-induced reconfiguration opens up an intriguing route towards actively controlled pixel arrays using local deformation, which fosters continuous polarization engineering and multi-channel detection.
CRIS-Team WoS Importer:2021-05-21

Nanoimprint Lithography Facilitated Plasmonic-Photonic Coupling for Enhanced Photoconductivity and Photocatalysis - Gupta, Vaibhav; Sarkar, Swagato; Aftenieva, Olha; Tsuda, Takuya; Kumar, Labeesh; Schletz, Daniel; Schultz, Johannes; Kiriy, Anton; Fery, Andreas; Vogel, Nicolas; König, Tobias A.F. (Advanced Functional Materials, 2021)
Imprint lithography has emerged as a reliable, reproducible, and rapid method for patterning colloidal nanostructures. As a promising alternative to top-down lithographic approaches, the fabrication of nanodevices has thus become effective and straightforward. In this study, a fusion of interference lithography (IL) and nanosphere imprint lithography on various target substrates ranging from carbon film on transmission electron microscope grid to inorganic and dopable polymer semiconductor is reported. 1D plasmonic photonic crystals are printed with 75% yield on the centimeter scale using colloidal ink and an IL-produced polydimethylsiloxane stamp. Atomically smooth facet, single-crystalline, and monodisperse colloidal building blocks of gold (Au) nanoparticles are used to print 1D plasmonic grating on top of a titanium dioxide (TiO2) slab waveguide, producing waveguide-plasmon polariton modes with superior 10 nm spectral line-width. Plasmon-induced hot electrons are confirmed via two-terminal current measurements with increased photoresponsivity under guiding conditions. The fabricated hybrid structure with Au/TiO2 heterojunction enhances photocatalytic processes like degradation of methyl orange (MO) dye molecules using the generated hot electrons. This simple colloidal printing technique demonstrated on silicon, glass, Au film, and naphthalenediimide polymer thus marks an important milestone for large-scale implementation in optoelectronic devices.
CRIS-Team Scopus Importer:2021-07-09
Keywords: colloidal nanospheres; nanoimprint lithography; photocatalysis; plasmon-induced charge transfer; waveguide-plasmon polariton

Plasmonic Charge Transfers in Large-Scale Metallic and Colloidal Photonic Crystal Slabs - Sarkar, Swagato; Gupta, Vaibhav; Tsuda, Takuya; Gour, Jeetendra; Singh, Arvind; Aftenieva, Olha; Steiner, Anja M.; Hoffmann, Marisa; Kumar, Sunil; Fery, Andreas; Joseph, Joby; Koenig, Tobias A. F. (Advanced Functional Materials, 2021)
The challenges in plasmonic charge transfer on a large-scale and low losses are systematically investigated by optical designs using 1D-plasmonic lattice structures. These plasmonic lattices are used as couplers to guide the energy in an underneath sub-wavelength titanium dioxide layer, resulting in the photonic crystal slabs. So far, photodetection is possible at energy levels close to the semiconductor bandgap; however, with the observed hybrid plasmonic-photonic modes, other wavelengths over the broad solar spectrum can be easily accessed for energy harvesting. The photo-enhanced current is measured locally with simple two-point contact on the centimeter-squared nanostructure by applying a bias voltage. As lattice couplers, interference lithographically fabricated conventional gold grating provides an advantage in fabrication; this optical concept is extended for the first time toward colloidal self-assembled nanoparticle chains to make the charge injection accessible for large-scale at reasonable costs with possibilities of photodetection by electric field vectors both along and perpendicular to the grating lines. To discuss the bottleneck of unavoidable isolating ligand shell of nanoparticles in contrast to the directly contacted nanobars, polarization-dependent ultrafast characterizations are carried out to study the charge injection processes in femtosecond resolution.
CRIS-Team WoS Importer:2021-03-19